Long-Term Immunological Alertness and Response to COVID-19 Vaccination-Conditions for Prevention in Early Palliative Oncological Care Patients - Priester, Peter; Fajfr, Miroslav; Molnarova, Veronika; Sleha, Radek; Janovska, Sylva; Bostik, Pavel; Filip, Stanislav (Vaccines, 2024)
Aside from the general population, the COVID-19 pandemic has also affected a group of patients in palliative oncology care. In this study, long-term immune responses against SARS-CoV-2 after vaccination were monitored in a cohort of patients in palliative oncology care. This non-randomized, prospective, and open-label pilot study recruited patients from the Palliative Oncology Program and included 147 patients, of which 80 were females (54.4%) and 67 males (45.6%). The overall evaluation included current health status, SARS-CoV-2 anti-S IgG titer, and neutralizing antibodies using the SARS-CoV-2 virus neutralization test (VNT). Anti-S IgG antibody analysis revealed high (H) antibody levels in 35.7% (n = 10) and very high (VH) levels in 39.3% (n = 11) of patients after the second vaccination dose. Similarly, after the third dose, H was found in 29.6% (n = 32) and VH in 55.5% (n = 60) of patients. High and very high anti-S IgG antibody levels were consistent with high VNT titers (>2560) and H antibody levels in 17.1% (n = 12) or VH in 82.9% (n = 58) of patients. Patients with two or more doses showed H and VH antibody levels at a median of 451 and 342 days after vaccination, respectively. In this clinical trial, patients showed high and very high levels of anti-S IgG antibodies over a longer period of time. These patients did not show reduced immunological responses to the COVID-19 vaccine challenge. We can assume that prevention through vaccination can reduce the risk of complications or death from COVID-19 in patients in early palliative oncology care.
Keywords: COVID-19 vaccine; VNT; inpatient care; anti-S IgG; palliative oncological care